Supply-policy coordination in a monetary union - Díaz Roldán, Carmen (Estudios Económicos de El Colegio de México, 2003)
This paper examines how the member countries of a large monetary union react to country-specific shocks, and to shocks from the rest of the world, using supply-side policies. We develop a three-country model in which two of the countries form a monetary union where an independent central bank to control monetary policy, and supply-side policies are determined by the authorities at the national level. In this framework, we analyse in strategic terms how the authorities can deal with monetary, real and supply shocks, and discuss the welfare aspects of the optimal solution and the extent to which a coordinated supply-side policy may be useful to deal with those shocks.